From Wood to Textiles: Top‐Down Assembly of Aligned Cellulose Nanofibers. Issue 30 (7th June 2018) - Jia, Chao; Chen, Chaoji; Kuang, Yudi; Fu, Kun; Wang, Yilin; Yao, Yonggang; Kronthal, Spencer; Hitz, Emily; Song, Jianwei; Xu, Fujun; Liu, Boyang; Hu, Liangbing
Abstract: Advanced textiles made of macroscopic fibers are usually prepared from synthetic fibers, which have changed lives over the past century. The shortage of petrochemical resources, however, greatly limits the development of the textile industry. Here, a facile top‐down approach for fabricating macroscopic wood fibers for textile applications (wood‐textile fibers) comprising aligned cellulose nanofibers directly from natural wood via delignification and subsequent twisting is demonstrated. Inherently aligned cellulose nanofibers are well retained, while the microchannels in the delignified wood are squeezed and totally removed by twisting, resulting in a dense structure with approximately two times higher mechanical strength (106.5 vs 54.9 MPa) and ≈20 times higher toughness (7.70 vs 0.36 MJ m −3 ) than natural wood. Dramatically different from natural wood, which is brittle in nature, the resultant wood‐textile fibers are highly flexible and bendable, likely due to the twisted structures. The wood‐textile fibers also exhibit excellent knitting properties and dyeability, which are critical for textile applications. Furthermore, functional wood‐textile fibers can be achieved by preinfiltrating functional materials in the delignified wood film before twisting. This top‐down approach of fabricating aligned macrofibers is simple, scalable, and cost‐effective, representing a promising direction for the development of smart textiles and wearable electronics. Abstract : Macroscopic wood fibers for textile applications with aligned cellulose nanofibers are fabricated by a facile top‐down approach directly from natural wood via delignification and subsequent twisting. The wood‐textile fibers exhibit high mechanical strength and toughness, excellent flexibility, knitting properties, dyeability, and promising multifunctionality for advanced textile applications.